PENGARUH PENERAPAN MODEL CONTROVERSIAL ISSUES (CI) TERHADAP PENINGKATAN KETERAMPILAN SOSIAL DAN HASIL BELAJAR SISWA YANG RESPONSIF GENDER - Edo Dwi Cahyo (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2018)
The purpose of this study was to determine the improvement of social skills and gender responsive students after the implementation of the Controversial Issues (CI) model in social studies learning while at the same time looking at student learning outcomes. The method of this research is the quasi-experimental method using the nonequivalent groups pretest-posttest design. The population is the fourth grade students of SD Negeri 8 Metro Timur with samples of classes IV A and IV B. Data collection techniques are in the form of tests and sets of students' social skills. The results of this study indicate that the Controversial Issues (CI) model in social studies learning can improve social skills and gender-responsive student learning outcomes.